Analisis Sosial dan Agama pada Praktik Pendistribusian Zakat Fitrah Bagi Dukun Bayi - Maskur, Maskur Maskur (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2021)
Zakat fitrah is a compulsory zakat that muslims neet to do. Zakat fitrah should be made to Amil zakat or the committee appointed to handle zakat. This is so taht distribution is even and right on terget. This study aims to analyze socially and religiously so that a common thread will be obtained about the suitability of zakat distribution practices in research location. This research is a qualitative study that describes the data in detail based on the findings in the field. The distribution of zakat for the dukun in Jamus village can be analyzed from social and religious analyzes, in addition to gratitude for the people who have been helped by the dukun, also on average the dukun helps with a sense of sincerity and with great selflessness. The social analysis is understood that most of the people who give zakat fitrah to the dukun are because of their emotional closeness because they have been helped a lot by the dukuns. In this case social interaction is very well guarded. Broadly speaking, the social values practiced by most people are based on the values of sympathy, empathy, and respect. Religious analysis in the practice of distributing zakat fitrah to traditional birth attendants in the Jamus village becomes invalid if it is intended for zakat fitrah, but if the gift is in the form of shodaqoh or infaq it may be done.